The Long Life and Swift Death of Jewish Rechitsa : A Community in Belarus, 1625-2000 - Kaganovich, Albert (Book collections on Project MUSE., 2013)
Located on the Dnieper River at the crossroads of Belarus, Russia, and Ukraine, the town of Rechitsa had one of the oldest Jewish communities in Belarus, dating back to medieval times. By the late nineteenth century, Jews constituted more than half of the town's population. Rich in tradition, Jewish Rechitsa was part of a distinctive Lithuanian-Belorussian culture full of stories, vibrant personalities, achievement, and epic struggle that was gradually lost through migration, pogroms, and the Holocaust. Now, in Albert Kaganovitch's meticulously researched history, this forgotten Jewish world is brought to life. Based on extensive use of Soviet and Israeli archives, interviews, memoirs, and secondary sources, Kaganovitch's acclaimed work, originally published in Russian, is presented here in a significantly revised English translation by the author. Details of demographic, social, economic, and cultural changes in Rechitsa's evolution, presented over the sweep of centuries, reveal a microcosm of daily Jewish life in Rechitsa and similar communities. Kaganovitch looks closely at such critical developments as the spread of Chabad Hasidism, the impact of multiple political transformations and global changes, and the mass murder of Rechitsa's remaining Jews by the German army in November to December 1941. Kaganovitch also documents the evolving status of Jews in the postwar era, starting with the reconstitution of a Jewish community in Rechitsa not long after liberation in 1943 and continuing with economic, social, and political trends under Stalin, Khrushchev, and Brezhnev, and finally emigration from post-Soviet Belarus. The Long Life and Swift Death of Jewish Rechitsa is a major achievement. Winner, Helen and Stan Vine Canadian Jewish Book Award for Scholarship, Koffler Centre of the Arts.